Féminismes et luttes contre l'homophobie: de l'apprentissage à la subversion des codes - Bard, Christine; Bastien Charlebois, Janik; Boisclair, Isabelle; Bourque, Dominique; Charbonneau, Amélie; Deshoulières, Étienne; Horincq Detournay, Rosine; Laprade, Bruno; Lebreton, Christelle; Maiorano, Sabrina; Ricard, Nathalie; Vallerand, Olivier (Les cahiers de l'IREF. Collection Agora, 2016)
En 1903, à Berlin, Anna Rueling appelait le mouvement homosexuel et le mouvement des femmes à s’entraider puisque tous deux luttaient pour la liberté et l’autodétermination individuelle. Plus d’un siècle plus tard, quelles convergences peut-on observer entre féminismes et luttes contre l’homophobie? Sur le plan de la pensée, quels rapprochements contemporains peut-on établir entre le champ des études féministes et celui de la diversité sexuelle et de genre? Comment s’articule l’intersection entre ces deux systèmes de différenciation hiérarchique que sont le sexisme et l’hétérosexisme ? Quels théories et concepts y circulent de manière transversale, et avec quelles redéfinitions? Ces questions ont guidé l’organisation du colloque «Féminismes et luttes contre l’homophobie: zones de convergence» tenu dans le cadre du congrès de l’ACFAS 2014 à l’Université Concordia, Montréal, le 16 mai 2014.
Keywords: amériques; approches et analyses; corps; cours; discipline; droit; empowerment; europe; france; homophobie; lesbianisme; pol5185; politique; pornographie; premier cycle; queer; québec; régions géographiques; science politique; science politique et droit; sciences humaines; sexualité; sociologie; thématiques; violences; violences contre les femmes*; violences sexistes et sexuelles

Sous le voile de la neutralité, un système sexiste. Analyse de la jurisprudence et de la législation en matière de prostitution au Canada - Chagnon, Rachel; Brière-Godbout, Léa (Service aux collectivités de l'UQAM/Concertation des luttes contre l'exploitation sexuelle, 2015)
Ce rapport vise à dresser un portrait des pratiques judiciaires en matière de criminalisation de la prostitution, de façon à justement mettre la question des rapports sociaux de sexe à l’avant-plan. Ce travail est exploratoire, notre étude s’étant limitée à un historique de la législation et à l’analyse de 128 décisions pratique de la prostitution. D’autre part, une seconde position défend l’idée d’une normalisation de l’industrie de la prostitution. On désire ici décriminaliser complètement la prostitution voire légaliser sa pratique au nom de la sécurité et de la lutte à la stigmatisation des prostituées. » (2015, 2)
Keywords: 2000 à aujourd'hui; 2010-2019; SAC; amériques; discipline; droit; droits des femmes*; prostitution; périodes historiques; québec; rapport; recherche partenariale; ressource en ligne; régions géographiques; science politique et droit; sexualité; thématiques

Beyond Gratification:The Benefits of Pornography and the Demedicalization of Female Sexuality - Jeneanne Orlowski (The Modern American, 2012)
This Paper argues that non-obscene adult pornography should remain protected by the United States Constitution because it has contributed to the demedicalization of female sexuality. There is an ongoing debate among feminists regarding the value of pornography and whether it should be protected under the First Amendment. This Paper explains the background of the debate regarding the status of pornography as a form of speech and whether it has value that warrants its protection. Specifically, this Paper focuses on the removal of nymphomania from the Diagnostic and Statistical Manual and its absence as a modern medical diagnosis as an example of the demedicalization of female sexuality. The demedicalization of female sexuality has positively affected women in the United States. Catalysts for this demedicalization include the production and consumption of adult pornography by women. For this reason, adult pornography deserves continued protection as a form of free speech under the First Amendment.
Keywords: amériques; corps; cours; discipline; droit; droits des femmes*; premier cycle; régions géographiques; santé; science politique et droit; sex1911; sexualité; sofia; thématiques; états-unis

In the days of our grandmothers: a reader in Aboriginal women's history in Canada - Kelm, Mary-Ellen; Townsend, Lorna (University of Toronto Press, 2006)
From Ellen Gabriel to Tantoo Cardinal, many of the faces of Aboriginal people in the media today are women. In the Days of Our Grandmothers is a collection of essays detailing how Aboriginal women have found their voice in Canadian society over the past three centuries. Collected in one volume for the first time, these essays critically situate Aboriginal women in the fur trade, missions, labour and the economy, the law, sexuality, and the politics of representation. (Midwest).
Keywords: 1700-1799; 1800-1899; 1900-1999; 2000 à aujourd'hui; 2000-2009; amériques; approches et analyses; canada; commerce; commerce de peaux; cours; discipline; droit; droits des femmes*; droits des femmes* autochtones; famille; féminisme autochtone; histoire; histoire et politique; pol4105; premier cycle; périodes historiques; régions géographiques; science politique et droit; sciences humaines; sexualité; thématiques; travail

Only words - MacKinnon, Catharine A. (Harvard University Press, 1993)
When is rape not a crime? When it's pornography--or so First Amendment law seems to say: in film, a rape becomes "free speech." Pornography, Catharine MacKinnon contends, is neither speech nor free. Pornography, racial and sexual harassment, and hate speech are acts of intimidation, subordination, terrorism, and discrimination, and should be legally treated as such. Only Words is a powerful indictment of a legal system at odds with itself, its First Amendment promoting the very inequalities its Fourteenth Amendment is supposed to end. In the bold and compelling style that has made her one of our most provocative legal critics, MacKinnon depicts a society caught in a vicious hypocrisy. Words that offer bribes or fix prices or segregate facilities are treated by law as acts, but words and pictures that victimize and target on the basis of race and sex are not. Pornography--an act of sexual domination reproduced in the viewing--is protected by law in the name of "the free and open exchange of ideas." But the proper concern of law, MacKinnon says, is not what speech says, but what it does. What the "speech" of pornography and of racial and sexual harassment and hate propaganda does is promote and enact the power of one social group over another. Cutting with surgical deftness through cases of harassment in the workplace and on college campuses, through First Amendment cases involving Nazis, Klansmen, and pornographers, MacKinnon shows that as long as discriminatory practices are protected as free speech, equality will be only a word.
Keywords: 1900-1999; 1990-1999; amériques; approches et analyses; cours; discipline; droit; histoire et politique; patriarcat; premier cycle; périodes historiques; régions géographiques; science politique et droit; sciences humaines; sciences sociales; sex1911; sexisme; sexualité; sofia; systèmes d'oppressions; thématiques; violences; états-unis; études de genres

Un genre trouble: le féminisme, la pornographie, la réforme du droit et la thèse de la reproduction de l'ordre social - Lacombe, D. (Déviance et société, 1992)
L'étude de la campagne de criminalisation de la pornographie au Canada, dans les années 1980, pose un défi au savoir conventionnel qui s'est développé, en sociologie et en criminologie, sur la réforme du droit. Ce savoir est l'argumentation selon laquelle les réformes, en dispersant le contrôle social, ne font que légitimer le système sans le modifier fondamentalement. Afin d'éviter l'essentialisme de ce savoir, j'ai utilisé une approche reflexive qui pense la relation entre la réforme du droit et le pouvoir comme à la fois contraignante et facilitante. L'établissement d'un lien entre la pornographie et la déviance sociale n'apparaît pas comme une construction sociale unifiée, mais comme un terrain contesté dans lequel se produisent des rapports de pouvoir complexes, et une multiplicité de stratégies de résistance. C'est dans ce sens que la réforme apparaît comme un mécanisme générateur des pratiques.
Keywords: 1900-1999; 1980-1989; amériques; approches et analyses; canada; cours; criminologie; discipline; droit; féminisme pop; justice sociale; pornographie; premier cycle; périodes historiques; ressource en ligne; régions géographiques; science politique et droit; sciences humaines; sex1911; sexualité; sociologie; thématiques

Pornography and civil rights: a new day for women's equality - Dworkin, Andrea; MacKinnon, Catharine A. (Organizing Against Pornography, 1988)
"Pornography is central in creating and maintaining the civil inequality of the sexes. Pornography is a systematic practice of exploitation and subordination based on sex which differentially harms women. . . ." With those bold words began the groundbreaking local antipornography law drafted by writer Andrea Dworkin and lawyer Catharine A. MacKinnon. Their completely new legal approach--in which pornography is defined as sex discrimination and therefore a violation of civil rights--would allow anyone injured by pornography to fight back by filing a civil lawsuit against pornographers. First passed in December 1983 in Minneapolis, where it was supported by a grassroots coalition of women, people of color, neighborhood groups, and the city's welfare poor and working poor, this law has transformed the way people of conscience understand the devastating impact of pornography on women's right to equality. This new law also offers hope: an effective legal tool for making sex equality real. In this comprehensive and easy-to-read guidebook, now available on line, the coauthors of the anti-pornography civil-rights ordinance explain: How pornography hurts women and how and why the civil-rights ordinance would make a difference. Why the pornography is so important to women's equality. The truth about the antipornography civil-rights ordinance--what it is, what it does, what it means, how it works. Answers to the lies about it--lies that the media have spread to protect the pornography industry. What you can do to stop the pornographers and further women's equality. "The Ordinance does not take 'rights' away from anyone, . . . it takes the power to hurt women away from pornographers." --from Pornography and Civil Rights
Keywords: 1900-1999; 1980-1989; amériques; approches et analyses; cours; discipline; droit; droits des femmes*; féminisme anti-porn; premier cycle; périodes historiques; rapports sociaux de sexe; régions géographiques; science politique et droit; sex1911; sexualité; sofia; thématiques; violences; états-unis

L'Envers de la nuit: les femmes contre la pornographie - Lederer, Laura; Audy, Monique; Dufresne, Martin (Collection Les Entêtées, 1983)
Keywords: 1900-1999; amériques; approches et analyses; corps; cours; discipline; droit; féminisme pop; premier cycle; psychologie; périodes historiques; régions géographiques; science politique et droit; sciences humaines; sex1911; sexisme; sexualité; systèmes d'oppressions; thématiques; violences; états-unis

Pornography, civil rights, and speech. (the 1984 Francis Biddle Memorial Lecture, Harvard Law School, April 5, 1984) (transcript) - MacKinnon, Catharine A. (Harvard Civil Rights-Civil Liberties Law Review)
Keywords: 1900-1999; 1980-1989; amériques; approches et analyses; corps; cours; discipline; droit; histoire et politique; patriarcat; premier cycle; périodes historiques; rapports sociaux de sexe; ressource en ligne; régions géographiques; science politique et droit; sex1911; sexisme; sexualité; systèmes d'oppressions; thématiques; violences; états-unis